2018
DOI: 10.3390/buildings8040060
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Social Client Relationship Management within the Nigerian Construction Industry

Abstract: Abstract:Client relationship management (CRM) has become a subject matter of interest to both academics and business practitioners. This is because it reflects the need to manage successful and profitable client relationships for organizations. Construction organizations, as well as the construction industry, are vital components of economic development in Nigeria, but many organizations struggle to perform the client relationships expected of them. The use of social media in the present era has given power to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Furthermore, social media (e.g., Twitter) can help to handle the complexity of soft and context-sensitive issues for modern urban infrastructure [81] because it encourages the micro-participation of numerous public stakeholders (i.e., citizens) [82]. Ninan et al [25] showed an example of how social media was strategically used to influence the project community, and Ojelabi et al [83] examined the social media practices of construction companies and concluded that their implementation is very basic, lacking the elements of serious stakeholder management based on social media. The challenges of using social media (i.e., Facebook, Twitter) for consulting and informing public stakeholders must be taken seriously because there is a risk of a perceived lack of responsiveness [78].…”
Section: Social Media As Modern Means To Engage Public Stakeholders and Internal Project Teammentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, social media (e.g., Twitter) can help to handle the complexity of soft and context-sensitive issues for modern urban infrastructure [81] because it encourages the micro-participation of numerous public stakeholders (i.e., citizens) [82]. Ninan et al [25] showed an example of how social media was strategically used to influence the project community, and Ojelabi et al [83] examined the social media practices of construction companies and concluded that their implementation is very basic, lacking the elements of serious stakeholder management based on social media. The challenges of using social media (i.e., Facebook, Twitter) for consulting and informing public stakeholders must be taken seriously because there is a risk of a perceived lack of responsiveness [78].…”
Section: Social Media As Modern Means To Engage Public Stakeholders and Internal Project Teammentioning
confidence: 99%
“…Social media has proven to be a modern tool for the engagement of various stakeholder groups because of its widespread usage for communication and sharing of various types of information. Ojelabi et al [83] concluded that social client relationship management (CRM 2.0) based on social media is not recognized in the construction sector, while it is often used in various other industries. According to this study [83], even if the concept of CRM 2.0 is implemented in a construction business, lack of control and lack of effective communication of protocols to employees are potential threats to business, which is in line with some other suggestions that it would be advisable to regulate and professionalize social media usage as a stakeholder management tool [77].…”
Section: Social Media As Modern Means Of Engagement For Public and Community Stakeholdersmentioning
confidence: 99%
“…The work [14] considers the social network analysis as well as content analysis of corporate social responsibility (sustainability) reports in relation to sustainable human resource management, taking into account the employee training of a wide range of enterprises. Another field of social media analysis could include client relationship management (CRM) using social media platforms studied in [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to classify the critical success factors (CSFs) enabling the social media infrastructure by SME construction businesses a factor analysis test was carried out. The thirteen (13) CSFs tested in this study were adapted for the study by Preece et al (2014) and Ojelabi et al (2018a). These CSFs focused on the use of the information and communication technologies (ICTs), the process involved and the human involvement in the process and acquisition.…”
Section: Critical Success Factors (Csf) Enabling the Social Media Infmentioning
confidence: 99%